Film landscapes of global youth - Aitken, Stuart C.; Rowlett, Jacob (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book explores the dynamic landscapes of global youth through spatially grounded chapters focused on film and media. It is a collection of incredible works concerning children and young people in, out and through media as well as an examination of what is possible for the future of research within the intersections of geography, film theory, and children's studies. It contains contributions from leading academics from film, media, and children's geographies, with chapters focused on a spatial area and the representations and relationships of children in that area through film and media. The insights presented also provides a unique and eclectic perspective on the current state of children's research in relation to the ever-changing media landscape of the 21st century. Imagining Young Lives approaches the subjects of children and young people in film and media in a way that is not bound by genre, format, medium, or the on/off-screen binary. Each chapter offers an insightful look at the relationships and portrayals of children and young people in relation to a specific country, culture, or geographic feature. This book is a must-read for anyone interested in the intersections between geography, young lives, and the power of film, television, social media, content creation, and more"--
Keywords: Mass media and youth; Youth in motion pictures; Geographical perception in children; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography